Checkpoint Inhibitor Immunotherapy for Head and Neck Cancer: Incorporating Care Step Pathways for Effective Side-Effect Management - Fazer, Casey (J Adv Pract Oncol, 2019)
The introduction of immunotherapy to treat recurrent/metastatic head and neck squamous cell carcinoma in 2016 has provided new valuable treatment options to many cancer patients. Pembrolizumab and nivolumab, which are classified as immune checkpoint inhibitors of programmed cell death protein 1, have shown clinically significant activity in patients who progressed on or after platinum-based regimens, and these agents are now US Food and Drug Administration approved for this indication. These treatments can result in unique immune-related adverse events (irAEs) that many health-care providers have difficulty identifying and managing. This article addresses the important role advanced practice providers play in a care team. Their experience is vital to managing the irAEs that can occur in patients being treated with immunotherapy agents. Their early experience with these newer therapies allows them to help educate and support not only patients but other health-care providers as well. The Care Step Pathways (CSPs) created as part of the Immuno-Oncology Essentials initiative are excellent tools to help with the diagnosis and management of many irAEs. This article summarizes the CSPs on specific considerations when managing thyroiditis, mucositis/xerostomia, skin toxicities, and hepatotoxicity, and addresses the special concerns of the head and neck squamous cell carcinoma population.